The methods of decodification of stylistic allusions (on the material of the novel Vanity Fair by W. Thackeray - N F Bystrikova; S B Tomashevich (Russian journal of linguistics: Vestnik RUDN, 2011)
The article examines the methods of decodification of stylistic allusion on the material of the novel Vanity Fair by W. Thackeray.